Penerapan Pendekatan Pakem untuk Meningkatkan Pemahaman Siswa Tentang Sifat-Sifat Bangun Ruang di Kelas IV SD Inpres I Nambaru - Ana Agung Made Ardani (Jurnal Paedagogy, 2020)
This study aims to create a conducive and pleasant learning atmosphere so that students can be directly involved in the learning process, through the application of the PAKEM approach to improve students' understanding of grade IV SD Inpres I Nambaru, South Parigi District, Parigi Moutong Regency in the material of building properties. By using the classroom action research method, it was concluded that: (a) The application of the PAKEM approach can improve the ability of Grade IV students of SD Inpres I Nambaru on the properties of building characteristics, (b) the PAKEM approach can be fun and motivate students in learning activities properties of building space. (c) The application of the PAKEM approach can lead to interest in leadership because in group learning researchers emphasize that the role of group leaders determines the success of each group, (d) The use of learning tools in this LKS greatly helps students in finding concepts.